Premarital sex among the Muslim youth in Malaysia / Laetitia Mughni M. Yussli…[et al.] - M. Yussli, Laetitia Mughni; Saiful Rizal, Nur Adlina Aleesha; Shaharudin, Nur Syazwani; Sarji, Nurul Atikah; Abdul Majid, Puteri Aida Sakeena (Faculty of Communication & Media Studies, 2019)
Islam recognizes the sexual needs of a human being for the purpose of procreation and pleasure. However, the fulfilment of sexual needs of Muslims must be made in a conscientious manner that is within the lawful framework of marriage. Premarital sex carries a lot of consequences, which explains why it is highly forbidden by most Muslim countries including Malaysia which involves one in high risk of sexually transmitted disease (STD) and HIV/AIDS. In Malaysia, There are over 257 million births listed exclusive of the father's name, which proves that premarital sex is an actively occurring activity. The main method used in this study is a semi-structured interview. This study adopts the cultivation theory that was proposed by George Gerbner in the 1960s and 1970s. According to the theory, people who watch television frequently tend to be influenced by the message it portrays. The findings revealed that the main drive of premarital sex activities is love and media. Post involvement in the activity shows that people were either regretful or happier with their action. The advice given to those who are thinking of involving or already involving is to have a stronger faith in religion, do not be easily influenced by peer pressure, develop self-control, implement sex education, set priorities and encourage early marriage.